(S-9)(s-1)=0

Simple and best practice solution for (S-9)(s-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (S-9)(s-1)=0 equation:


Simplifying
(S + -9)(s + -1) = 0

Reorder the terms:
(-9 + S)(s + -1) = 0

Reorder the terms:
(-9 + S)(-1 + s) = 0

Multiply (-9 + S) * (-1 + s)
(-9(-1 + s) + S(-1 + s)) = 0
((-1 * -9 + s * -9) + S(-1 + s)) = 0
((9 + -9s) + S(-1 + s)) = 0
(9 + -9s + (-1 * S + s * S)) = 0
(9 + -9s + (-1S + sS)) = 0

Reorder the terms:
(9 + -1S + -9s + sS) = 0
(9 + -1S + -9s + sS) = 0

Solving
9 + -1S + -9s + sS = 0

Solving for variable 'S'.

Move all terms containing S to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -1S + -9s + -9 + sS = 0 + -9

Reorder the terms:
9 + -9 + -1S + -9s + sS = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -1S + -9s + sS = 0 + -9
-1S + -9s + sS = 0 + -9

Combine like terms: 0 + -9 = -9
-1S + -9s + sS = -9

Add '9s' to each side of the equation.
-1S + -9s + 9s + sS = -9 + 9s

Combine like terms: -9s + 9s = 0
-1S + 0 + sS = -9 + 9s
-1S + sS = -9 + 9s

Reorder the terms:
9 + -1S + -9s + sS = -9 + 9s + 9 + -9s

Reorder the terms:
9 + -1S + -9s + sS = -9 + 9 + 9s + -9s

Combine like terms: -9 + 9 = 0
9 + -1S + -9s + sS = 0 + 9s + -9s
9 + -1S + -9s + sS = 9s + -9s

Combine like terms: 9s + -9s = 0
9 + -1S + -9s + sS = 0

The solution to this equation could not be determined.

See similar equations:

| r+9r=-8 | | 18j-5=3(6j-2) | | 150=c+.18c | | 4x+(-8x)= | | a+75=-1+9 | | 81650.99=2*3.14*2*r+2*3.14*r*287.9 | | 3h+1=3(h-1)+4 | | 188.9024=64.3072+20.069h | | 14x+4x=38 | | 4x^2-14x= | | 4x+a=-6 | | 4(2x+3)=21 | | 81650.99=2*3.14*2*r+2*314*r*287.9 | | 1/5b+19=3/5b-27 | | 9t^2+5=14t | | 15=7+10w | | c=25.34+.06*25.34 | | 15x-3-x=3x | | 218.75=35t-.7t^2 | | 3+8(x)=-29 | | 10m+8=6m-10 | | 1/4(72-6a)=-30 | | x*7=1200 | | 168=150(1+0.08) | | 3(x-3)+2=26 | | 580.586=2*3.14*18.49+2*3.14*4.3*h | | -3+8(1-2x)=4x-15 | | 3k+y=1 | | 2w+6x-y+8w-21x-7y= | | 95r=1995 | | -69v=-3450 | | (2+0.50)=10 |

Equations solver categories